PENGGUNAAN ASAS-ASAS FILOSOFIS DALAM PENGEMBANGAN DAN PELAKSANAAN KURIKULUM MERDEKA - Cintya Permatasari Pata’dungan; Misel Pilemon; Noflianti Rapang; Mari Manggauali; Dina Dina (CV. ADIBA AISHA AMIRA, 2023)
This research aims to analyze the use of philosophical principles in the development and implementation of the